Novel technique for lateral high‐voltage totem‐pole power devices. Issue 9 (1st September 2014) - Kong, Moufu; Chen, Xingbi
Abstract : A novel technique and related structure for a high‐voltage integrated circuit (IC) with totem‐pole high‐voltage devices are proposed. In this technique, a low control voltage with respect to the tub is used to drive the high‐side device in the totem pole through a low‐voltage tub circuit, as well as through very small low‐side device to drive a low‐voltage ground circuit, which in turn drives the low‐side device in the totem pole. Therefore, the high‐voltage level‐shifting circuit can be replaced by the tub circuit which takes only a very small area and has no parasitic effects in comparison with that in the conventional totem‐pole high‐voltage IC. The structure of low‐voltage power supplies for low‐voltage ICs is also proposed. The results of numerical simulation verify the applicability of the proposed structure.